COPPER ADSORPTION IN TWO DIFFERENT SOIL TEXTURE - & et al., Al-Hassoon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was conducted to study the physico-chemical behavior of copper in predominance soil orders (Entisols) Jadriya and Najaf of Iraq . Two different locations were chosen according to the variation in their soil orders and physical and chemical properties. Cu adsorption phenomenon were carried out to study copper adsorption using two different soil textures of the surface layer 0-0.3 m with clay loam for the Jadriya site, University of Baghdad and the second (sandy loam) to the site of Najaf by using batch equilibrium at (298 o Kelvin) . Langmuir equation was used to describe the copper adsorption processes in the studied soils. Diffusion Coefficient, the Maximum Buffering Capacity, the Equilibrium Buffering Capacity and the Supplying Parameter in soil .The main results could be summarized as follows, the adsorption equation Langmuir obtained the highest values of the R2 in the description of copper isotherm adsorption in both soil , the Diffusion Coefficient value ranged widely from 8316-14476 ml gm-1 with, copper maximum adsorption 5000 -10000 mmol kg-1, bonding energy values were 0.13-1.43 L mmol-1, Maximum Buffering Capacity was ranged between 667 to 14286 L kg-1, the copper Equilibrium Buffering Capacity 656 to 11960 L kg-1, Cu-Supplying Parameter in two soils were ranging from 0.67 to 1.36 Thermodynamic parameters of copper adsorption, the diffusion coefficient (RL), 0.07 to 0.06, and Gibss free energy are negative values and are consistent with diffusion coefficient values that are less than (1) 0.018 to 0.203 (Kj mol. kelvin-1), for the two soil textures respectively , which means that the reaction of the adsorbed copper is spontaneous reaction.